Efeitos da suplementação de zinco sobre o perfil lipídico de ratas ovariectomizadas submetidas a treinamento físico com carga - Silva, Talita Maria Alves Lopes da (2011)
Ovariectomy, removal of the ovaries, contributes to the lack of estrogen and thus is a good model to represent a decrease of this hormone that occurs at menopause, making women more prone to diseases and symptoms of this phase. After menopause can observe increased oxidative stress in women, a result of the imbalance of the immune system, oxidative stress that may occur due to the influence that estrogen has on the immune system and its antioxidant action. In this scenario zinc is considered an important element, since it acts as a cofactor of several antioxidant enzymes. The aim of this study was to evaluate the effects of zinc supplementation with or without physical training load on lipid profile and spleen mass of ovariectomized rats. This is an experimental study 60 wistar rats were divided into five groups with 12 animals each, and these groups called SHAM (not ovariectomized and untreated), OX-C (ovariectomized without treatment), OX-Z (ovariectomized supplemented zinc), OX-TF (ovariectomized subjected to physical activity) and OX-ztf (ovariectomized supplemented with zinc and subjected to physical activity). The protocol consisted of 04 2 ° C at a±sets of 10 jumps into the water, at temperatures of 32 depth of 70 cm and 30-second intervals between sets, we used an overhead attached to a specific vest. In the first and second weeks of training was added overhead of 50% of body weight of rats in the third and fourth weeks, 60%, fifth and sixth weeks and 70% in the last two weeks 80% of body weight. The training of the animals was performed three times per week during the eight weeks, which coincided with the period of zinc supplementation. After euthanasia, we analyzed lipid profile (total cholesterol, LDL, HDL, VLDL, triglycerides), weight of organs (spleen, heart and uterus) and body fat. The parameters were analyzed by unpaired t-test and univariate ANOVA. The results on the mass of the uterus and levels of estradiol of ovariectomized animals were significantly lower than control group. The suppression of estrogen increased the feed intake (p = 0.0001) and body mass (p = 0.0002), however the groups supplemented with zinc had lower values of these data when compared with the group X-C (p = 0 , 0001 / 0.01 respectively). The mass of the spleen of ovariectomized animals with no treatment was significantly higher than the SHAM (p = 0.04), while the OX-ztf group, compared with OX-C showed a smaller mass of the spleen (p = 0.02). We observed that estrogen increased the suppression all serum concentrations evaluated, with statistical difference only for the concentrations of total cholesterol and LDL. Zinc treatment decreased concentrations of VLDL and triglycerides and increased HDL, total cholesterol and LDL. Since physical training decreases all dosages, except for HDL. Then it was observed that zinc with or without exercise training was presented as an option to mitigate the physiological disorders caused by suppression of estrogen on lipid profile in ovariectomized rats.